Sistem Informasi Manajemen Proyek Informatika Berbasis Web untuk Optimalisasi Kinerja Tim dan Pengambilan Keputusan - Burhan Firdaus; Dzaky Setiawan Tauri; Muhamad Rizki Al-Baras; Samsudin Samsudin; Ahmad Nursodiq (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
An effective project management system is a crucial need in software development and other IT projects. This study aims to design and evaluate a web-based project management information system with integration of collaboration, scheduling, and reporting features based on real-time data. This study adopts a combined approach from three previous studies, namely a NodeJS-based collaboration system, a CodeIgniter project management system, and a PERT-based evaluation approach. The implementation results show increased teamwork efficiency, reporting accuracy, and managerial ability to anticipate project obstacles. This system is suitable for application in various scales of IT projects.